YouTube as a source of information on varicose veins. (August 2016) - Güneş, Tevfik; Serinken, Mustafa; Alur, İhsan; Beydilli, Halil; Karcioglu, Ozgur; Eken, Cenker
Background: There has been little investigation of videos related to varicose veins in Internet media. This study aimed to investigate the characteristics and scientific accuracy of the videos related to varicose veins which were uploaded to the youtube.com website. Methods: The YouTube site was searched in October 2014 using the keywords varicose vein, varicose veins, and varicosis with no filter. The contents of the reviewed videos were assigned to three groups as useful, partly useful, and not useful by using the criteria including the scientific contents of the videos, contemporariness and accuracy of the insight, and presentation of the data particularly regarding the visual features. The statistical analysis was based only on the videos rated as 'useful.' Results: In total, 1519 (84.4%) of 1800 videos evaluated were excluded. Many of the sources uploading videos to the website were healthcare professionals (32.7% n  = 92). Regarding the source of the upload, those from official institutions/associations were viewed statistically significantly more often than videos uploaded by all others ( p  = 0.001). The rated usefulness was significantly higher for videos uploaded by official institutions/associations (100%) than those uploaded by others ( p  = 0.01). Conclusions: Official institutions/associations should be encouraged to produce and upload videos including up-to-date and comprehensive information regarding the disease. Likewise, additional search tools would be useful to locate videos uploaded by academic figures and institutions.